Climate change impacts on asphalt road pavement construction and maintenance: An economic life cycle assessment of adaptation measures in the State of Virginia, United States. (20th August 2019) - Qiao, Yaning; Santos, Joao; Stoner, Anne M.K.; Flinstch, Gerardo
Abstract: Pavement design and management practices must be adapted in response to future climate change. While many studies have attempted to identify different methods to adapt pavements to future climate conditions, the potential economic impacts of the adaptations still remain largely unquantified. This study presents the results of a comprehensive life‐cycle cost analysis (LCCA) aimed at quantifying the potential economic impacts of a climate adaptation method, in which an upgraded asphalt binder (Performance Grade PG 76‐22) is used in the construction and maintenance of flexible pavement sections in lieu of the original binder (PG 70‐22) for improved resistance against high temperatures. For each of three major Virginia Department of Transportation (VDOT) districts with different climates, three case studies consisting of typical interstate, primary, and secondary pavement sections were considered. The LCCA accounted for the costs incurred during the mixture's production, maintenance, and use phases of the pavement life cycle by explicitly considering future climate projections, pavement life‐cycle performance, maintenance effects, and work zone user delays. The study concludes that pavements using the upgraded binder not only perform better over time but are also economically advantageous compared to those with the original binder under the conditions of the anticipated future climate conditions (2020–2039).